Design, synthesis, and apoptosis-promoting effect evaluation of novel pyrazole with benzo[d]thiazole derivatives containing aminoguanidine units - Da Chuan Liu; Mei Jia Gao; Qiang Huo; Tao Ma; Ying Wang; Cheng Zhu Wu (Taylor & Francis Group, 2019)
New pyrazole with benzo[d]thiazoles containing hydrazinecarboximidamide substituent was synthesised and evaluated for cytotoxicity and apoptotic activity using the MTT assay, flow cytometry, and Western blot analysis. Among the compounds studied, (E)-2-((1-(6-((4-fluorobenzyl)oxy)benzo[d]thiazol-2-yl)-3-phenyl-1H- pyrazol-4-yl)methylene) hydrazinecarboximidamide (8l) was potent, with IC50 values of 2.41 µM, 2.23 µM, 3.75 µM and 2.31 µM in vitro anti-proliferative activity testing against triple-negative breast cancer cell line MDA-MB-231, non-triple-negative breast cancer MCF-7 cells, and human hepatocarcinoma HepG2 cells, and SMMC-7721 cells, respectively. Especially, the activity against MDA-MB-231 was similar to that of Doxorubicin, which was used as a positive control in this study. Next, the Annexin V/PI flow cytometry assay was used at different concentrations of compound 8l to demonstrate that compound 81 induced apoptosis of MDA-MB-231 cells in a concentration-dependent manner. Finally, these results were further verified by Western blot analysis. Taken together, the results of this study revealed that compound 8l may be a potential anticancer compound play a significant role in the subsequent researches.